Modulating the Surface State of SiC to Control Carrier Transport in Graphene/SiC. Issue 26 (28th May 2018) - Jia, Yuping; Sun, Xiaojuan; Shi, Zhiming; Jiang, Ke; Liu, Henan; Ben, Jianwei; Li, Dabing
Abstract: Silicon carbide (SiC) with epitaxial graphene (EG/SiC) shows a great potential in the applications of electronic and photoelectric devices. The performance of devices is primarily dependent on the interfacial heterojunction between graphene and SiC. Here, the band structure of the EG/SiC heterojunction is experimentally investigated by Kelvin probe force microscopy. The dependence of the barrier height at the EG/SiC heterojunction to the initial surface state of SiC is revealed. Both the barrier height and band bending tendency of the heterojunction can be modulated by controlling the surface state of SiC, leading to the tuned carrier transport behavior at the EG/SiC interface. The barrier height at the EG/SiC(000‐1) interface is almost ten times that of the EG/SiC(0001) interface. As a result, the amount of carrier transport at the EG/SiC(000‐1) interface is about ten times that of the EG/SiC(0001) interface. These results offer insights into the carrier transport behavior at the EG/SiC heterojunction by controlling the initial surface state of SiC, and this strategy can be extended in all devices with graphene as the top layer. Abstract : The initial surface state of silicon carbide (SiC) substrate is proved to be the key factor which can be used to modulate the interfacial band structure between graphene and SiC substrate. This result provides a way to control the carrier transport at interface and improve the performance of devices based on epitaxial graphene (EG)/SiC material.